Bismuth ferrite-barium titanate based piezoelectric ceramic and preparation method thereof
By adjusting the content of BiFeO3 and BaTiO3 and quenching treatment, the proportion and microstructure of bismuth ferrate-barium titanate piezoelectric ceramics are optimized, and the problem of limited improvement in piezoelectric performance in the existing technology is solved, and efficient improvement in piezoelectric performance and ceramic materials suitable for high-temperature applications are achieved.
Patent Information
- Application Number
- CN202510112519.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The piezoelectric properties of existing bismuth ferrate-barium titanate piezoelectric ceramics are limited in improvement and the preparation process is complex, making it difficult to directly replace traditional lead-containing piezoelectric ceramics.
By adjusting the content of components BiFeO3 and BaTiO3, maintaining the proportional close energy barrier reduction, promoting domain flip, and combining quenching treatment, the microstructure and performance of the ceramic are optimized.
It significantly improves the piezoelectric properties of bismuth ferrate-barium titanate piezoelectric ceramics, with a piezoelectric coefficient up to 228 pC/N, and is suitable for high-temperature sensor materials.
Smart Images

Figure CN119874344A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramics, and in particular to a bismuth ferrite-barium titanate-based piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics can realize the mutual conversion between electrical energy and mechanical energy. They are important functional materials for completing technologies such as mechatronics and intelligent structural components. They are widely used in electronic equipment, automotive industry, aerospace and other fields. Among them, bismuth ferrite-barium titanate (BiFeO3-BaTiO3, BFO-BTO) lead-free piezoelectric ceramics are a new generation of environmentally friendly materials. They have excellent piezoelectric properties and high Curie temperature, and have attracted attention as high-temperature lead-free piezoelectric ceramics. Although bismuth ferrite-barium titanate piezoelectric ceramics have the above advantages, they also have some disadvantages: (1) Compared with traditional lead-containing piezoelectric ceramics (such as lead zirconate titanate PZT), the piezoelectric coefficient of BiFeO3-BaTiO3 is generally lower, which means that it may not be a direct replacement for lead-containing materials in applications that require high piezoelectric response.
[0003] (2) BiFeO3 itself has a complex crystal structure in its pure state and is prone to form impurity phases, which affect the properties of the final ceramic.
[0004] (3) In order to obtain high-performance BFO-BTO ceramics, it is often necessary to carefully control the synthesis conditions, including parameters such as temperature and atmosphere, and the preparation process is complicated.
[0005] In order to solve the above shortcomings of BiFeO3-BaTiO3 piezoelectric ceramics, the following methods are often used: (1) By introducing an appropriate amount of dopants into BiFeO3 or BaTiO3, such as rare earth elements (La, Nd, etc.), transition metal ions or other elements, the structural stability and piezoelectric properties of the material can be effectively improved, while reducing leakage current and improving fatigue resistance.
[0006] (2) The use of advanced synthesis techniques, such as sol-gel method, hydrothermal synthesis, solid-phase reaction method, etc., can more accurately control the chemical composition and microstructure of the material, thereby improving the consistency and reproducibility of the material. In addition, atmosphere control and temperature management during the sintering process are also key factors.
[0007] Chinese Patent CN113292329B discloses a bismuth ferrite-barium titanate binary high-temperature piezoelectric ceramic material, its preparation method and application. The chemical composition of the piezoelectric ceramic material is (1-x)BiFeO3-xBaTiO3, where 0 < x < 1. Coarse bismuth ferrite-barium titanate powder and fine bismuth ferrite-barium titanate powder with a particle size difference of 700 nm to 1.2 μm are used as raw materials. Bismuth ferrite-barium titanate is prepared using a mixed powder of different particle sizes. Since the surface tension between large particles and small particles is greater than the surface tension between the same particles when they come into contact, it is more conducive to the growth of grains, resulting in an increase in the relative density of the ceramic material and a decrease in the porosity, thereby improving the dielectric constant and piezoelectric coefficient of the ceramic material.
[0008] Chinese Patent CN114180950A discloses a method for preparing bismuth ferrite-barium titanate (BiFeO3-BaTiO3) ceramics by two-step sintering. Weigh according to the chemical formula (1-x)Bi (1+y) FeO 3- xBaTiO3, ball-mill and mix the materials, dry them, and after sieving, place them in an alumina crucible. Pre-sinter at 780 - 950 °C for 2 - 12 h to obtain pre-sintered powder; then perform secondary ball-milling, and then dry at 70 - 120 °C. Add 2 wt% concentration of polyvinyl alcohol to the sieved dry powder and grind and granulate. Put the granulated powder into a mold and press it into shape; place the ceramic green body in a muffle furnace, heat it to 300 - 440 °C, degrease for 2 - 4 h, then heat it to 950 - 1060 °C, keep it warm for 1 - 10 min, cool it to 900 - 1060 °C, sinter for 4 - 12 h, and cool it to room temperature with the furnace to prepare the required ceramics. The two-step sintering method can avoid the temperature range for the formation of impurity phases in bismuth ferrite-barium titanate ceramics by skillfully controlling the two-step sintering temperature and holding time. The prepared ceramics have good crystallinity, uniform composition, small grain size, dense structure, and excellent piezoelectric and photovoltaic properties.
[0009] The above methods have respectively improved the piezoelectric properties of BiFeO3-BaTiO3 piezoelectric ceramics by designing the particle size of raw materials, component design, or improving the preparation method. However, due to the preparation of piezoelectric ceramics using only a single modification method, the improvement of piezoelectric properties is limited. There is an urgent need for a method that can synergistically combine multiple modification methods to greatly improve the piezoelectric properties of BiFeO3-BaTiO3. Summary of the Invention
[0010] The purpose of the present invention is to provide a bismuth ferrite-barium titanate-based piezoelectric ceramic and its preparation method to solve the problem that the modification method of BiFeO3-BaTiO3 piezoelectric ceramics is relatively single and the improvement of piezoelectric properties is limited.
[0011] To achieve the above object, the present invention provides a bismuth ferrite-barium titanate-based piezoelectric ceramic in the first aspect. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic is (1-x)BiFe (1-y) Co y O3-xBaTiO3, where 0.3≤x≤0.4, 0.001≤y≤0.004.
[0012] Preferably, 0.303≤x≤0.330.
[0013] Preferably, 0.310≤x≤0.330.
[0014] Preferably, the piezoelectric coefficient of the bismuth ferrite-barium titanate-based piezoelectric ceramic is 170-228 pC / N.
[0015] More preferably, the piezoelectric coefficient of the bismuth ferrite-barium titanate-based piezoelectric ceramic is 210-228 pC / N.
[0016] A second aspect of the present invention provides a method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic, comprising the following steps: (1) Using Fe2O3, Bi2O3, BaCO3, TiO2, and Co2O3 powders as raw materials, according to the stoichiometric ratio (1-x)BiFe (1-y) Co y O3-xBaTiO3 is prepared and mixed to obtain raw material powder; (2) synthesizing and finely grinding the raw material powder to obtain ceramic powder; (3) The ceramic powder is sequentially subjected to granulation, blanking, plasticizing, sintering and air quenching to obtain bismuth ferrite-barium titanate based piezoelectric ceramics.
[0017] During the preliminary research, the inventor first thought that ion doping would inevitably cause the phase ratio to change, deviate from the initial optimal ratio, and thus affect the performance. The present invention can adjust the content of the components BiFeO3 and BaTiO3 to adjust the phase ratio within the quasi-isotropic phase boundary, so that the ratio of the two phases is close to the energy barrier, which promotes the flipping of the electric domain and achieves the purpose of optimizing performance. Furthermore, the inventors considered that quenching treatment will increase the content of the rhombohedral phase and reduce the tetragonal phase in the material while reducing defects, so it is possible to select samples close to the tetragonal phase for quenching treatment, that is, to maintain its optimal phase ratio while reducing the defect concentration, thereby achieving a significant improvement in the piezoelectric performance of the sample.
[0018] Based on the above two considerations, the inventors creatively selected a compound having a chemical formula of (1-x)BiFe (1-y) Co yBismuth ferrite-barium titanate-based ceramics of O3-xBaTiO3 are used as the matrix, and on this basis, components tending to the tetragonal phase are selected according to the above method for air quenching.
[0019] The present invention shows that in bismuth ferrite-barium titanate piezoelectric ceramic materials, when the ratio of the two phases is close, the energy barrier is reduced to promote the flipping of the electric domain, and the performance of the piezoelectric ceramic material reaches the best. The content of the tetragonal phase is higher in the components with a high content of BaTiO3. By purposefully selecting components that tend to be tetragonal for quenching, the performance of the material can be greatly improved. In the present invention, the two piezoelectric ceramic modification methods of component regulation and process optimization are combined, and the two work synergistically to significantly improve the piezoelectric performance of bismuth ferrite-barium titanate piezoelectric ceramic materials.
[0020] Preferably, in step (1), the mixing process is wet ball milling, and the wet ball milling comprises the following steps: Add raw materials, ball milling media and deionized water into a ball mill for ball milling until they are uniformly mixed; the mass ratio of raw materials, ball milling media and deionized water is 1: (1.6-2.4): (0.8-2); the ball milling speed is 300-400 rpm, and the ball milling time is 20-24 hours.
[0021] Preferably, in step (2), the synthesis temperature is 700-850° C., the holding time is 4-6 hours, and the synthesis heating rate is 4-6° C. / min.
[0022] Preferably, in step (2), the fine grinding process is wet ball milling, and the wet ball milling comprises the following steps: The synthesized powder, ball milling medium and deionized water are added into a ball mill for ball milling until they are uniformly mixed; wherein the mass ratio of the synthesized powder, ball milling medium and deionized water is 1:(1.6~2.4):(0.8~2); the ball milling speed is 300~400 rpm, and the ball milling time is 20~24 hours.
[0023] Preferably, in step (3), during the granulation process, a binder in an amount of 5% to 10% by weight of the ceramic powder is added for granulation; the binder is a 4 to 8 wt.% polyvinyl alcohol solution; The green body is made by pressing the powder into a green body with simple mechanical pressure, the molding pressure is 15~20Mpa, and the green body size is 12~14mm in diameter and 1~2mm in thickness; The temperature of plastic discharge is 600~800℃, and the heat preservation time is less than 3 hours; the heating rate of plastic discharge is ≥2℃ / minute.
[0024] Preferably, in step (3), the temperature of the binder removal is 600-800°C, and the temperature is kept for less than 3 hours; the heating rate of the binder removal is 4-6°C / min.
[0025] Preferably, in step (3), the sintering temperature is 980-1030° C., and the sintering time is 2-5 hours.
[0026] Preferably, in step (3), the air quenching temperature is 800-970°C, the time is 20-60 minutes, and the steel sheet is taken out of the furnace directly after the quenching is completed.
[0027] Therefore, the present invention adopts the above-mentioned bismuth ferrite-barium titanate-based piezoelectric ceramic and its preparation method, which has the following beneficial effects: (1) The present invention regulates the components in bismuth ferrite-barium titanate-based piezoelectric ceramics on the one hand, and optimizes the preparation method on the other hand. These two aspects work together to significantly improve the piezoelectric properties of bismuth ferrite-barium titanate-based piezoelectric ceramics, with the piezoelectric coefficient reaching up to 228 pC / N.
[0028] The present invention adopts a solid phase method to prepare, and the piezoelectric properties of the bismuth ferrite-barium titanate lead-free piezoelectric ceramic material are regulated by changing the BaTiO3 content and then performing a quenching process. Since the ion doping of the bismuth ferrite-barium titanate ceramic material will inevitably cause the phase ratio to change, deviating from the initial optimal ratio, thus affecting the performance. The present invention adjusts the content of BaTiO3 in the formula and selects samples close to the tetragonal phase area for quenching treatment, that is, maintaining its optimal phase ratio while reducing the defect concentration, thereby achieving a significant improvement in the piezoelectric performance of the sample.
[0029] (2) The present invention prepares ceramic materials through a traditional solid-phase reaction method, which has a simple process, easy-to-control parameters, low cost, and is easy for industrial production.
[0030] (3) The piezoelectric ceramic material prepared by the present invention has the characteristics of high piezoelectric performance and high Curie temperature, and is suitable for application in high-temperature sensor materials, meeting the application requirements of high-temperature piezoelectric ceramic devices.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 XRD patterns of the lead-free piezoelectric ceramics prepared in Examples 1 to 7; Figure 2 The piezoelectric properties of the lead-free piezoelectric ceramics prepared in Examples 1 to 7 before and after quenching. DETAILED DESCRIPTION
[0033] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0034] Example 1 A method for preparing bismuth ferrite-barium titanate-based piezoelectric ceramics comprises the following steps: (1) Component regulation The chemical formula of bismuth ferrite-barium titanate based piezoelectric ceramics is as follows: 0.697BiFe 0.998 Co 0.002 O3-0.303BaTiO3; (2) Analytically pure Fe2O3, Bi2O3, BaCO3, TiO2 and Co2O3 were used as raw materials, and the ingredients were prepared and mixed according to the target chemical composition. The raw materials were mixed evenly by wet ball milling and dried. Specifically, the raw materials: zirconium balls: deionized water were mixed in a ratio of 1:2:2. The ball milling speed was 350 rpm, and the mixture was planetary ball milled for 24 hours. After drying at 100°C, the raw material powder was passed through an 80-mesh sieve to obtain the raw material powder.
[0035] (3) Pre-sintering the raw material powder in an alumina crucible, heating it to 800°C at a rate of 5°C / min, keeping it at that temperature for 5 hours, and then cooling it to room temperature with the furnace to obtain a material block; The synthesized material block was mechanically crushed, passed through an 80-mesh sieve, and then finely ground for 24 hours at a ratio of synthesized powder: zirconium ball: deionized water = 1:2:2, with a ball mill speed of 400 rpm. After drying at 100°C, ceramic powder was obtained.
[0036] (4) Add 5% binder (8% polyvinyl alcohol (PVA) solution) by weight of the dried ceramic powder to granulate the powder, sieve through an 80-mesh screen, press into a green body at a pressure of 20 MPa.
[0037] (5) heating the green body to 600°C at a rate of 5°C / min and maintaining the temperature for 2 hours to discharge the green body, thereby obtaining a ceramic green body; (6) In order to prevent the volatilization of bismuth elements, the ceramic blank is placed in an alumina crucible, covered with ceramic powder of the same composition as in step (3), covered with a ground lid, heated to 1000°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, sintered, and cooled to room temperature in the furnace to obtain a composite material; (7) After the sintered composite material is heated to 900°C at a rate of 5°C / min and kept at this temperature for 1 hour, the furnace door is opened and the composite material is placed in air for rapid quenching to obtain bismuth ferrite-barium titanate-based piezoelectric ceramics; (8) The quenched ceramic material is processed and cleaned, and then screen printed to prepare double-sided silver paste electrodes. The temperature is raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 30 minutes to obtain a ceramic component.
[0038] The ceramic element obtained before and after quenching in Example 1 was polarized at 85°C and 40 kV DC voltage. The polarized sample was left to stand for 24 hours and the piezoelectric coefficient d 33 Test, piezoelectric coefficient d33 By quasi-static 33 The ceramic component before quenching refers to the process of directly subjecting the composite material obtained in step (6) to the ceramic component preparation process in step (8) without the air quenching step in step (7).
[0039] The XRD pattern of the sample before quenching and the piezoelectric coefficient d of the sample before and after quenching prepared in Example 1 33 The images are Figure 1 and Figure 2 The piezoelectric coefficient d of the bismuth ferrite-barium titanate-based piezoelectric ceramics prepared in Example 1 is 33 218pC / N, increasing d 33 It is 10pC / N.
[0040] Example 2 The difference between the embodiment and embodiment 1 is that the component regulation is different. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic in this embodiment is as follows: 0.695BiFe 0.998 Co 0.002 O3-0.305BaTiO3.
[0041] XRD spectrum of the bismuth ferrite-barium titanate-based piezoelectric ceramic material prepared in Example 2 and the piezoelectric coefficient d before and after air quenching 33 The images are Figure 1 and Figure 2 The piezoelectric coefficient d of the bismuth ferrite-barium titanate-based piezoelectric ceramics prepared in Example 2 is 33 220pC / N, increasing d 33 It is 15pC / N.
[0042] Example 3 The difference between the embodiment and embodiment 1 is that the component regulation is different. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic in this embodiment is as follows: 0.693BiFe 0.998 Co 0.002 O3-0.305BaTiO3.
[0043] XRD spectrum of the bismuth ferrite-barium titanate-based piezoelectric ceramic material prepared in Example 3 and the piezoelectric coefficient d before and after air quenching 33 The images are Figure 1 and Figure 2 The piezoelectric coefficient d of the bismuth ferrite-barium titanate-based piezoelectric ceramics prepared in Example 3 is 33 224pC / N, increasing d 33 It is 21pC / N.
[0044] Example 4 The difference between the embodiment and embodiment 1 is that the component regulation is different. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic in this embodiment is as follows: 0.690BiFe 0.998 Co 0.002 O3-0.310BaTiO3.
[0045] XRD spectrum of the bismuth ferrite-barium titanate-based piezoelectric ceramic material prepared in Example 4 and the piezoelectric coefficient d before and after air quenching 33 The images are Figure 1 and Figure 2 The piezoelectric coefficient d of the bismuth ferrite-barium titanate-based piezoelectric ceramics prepared in Example 4 is 33 217pC / N, increasing d 33 It is 37pC / N.
[0046] Example 5 The difference between the embodiment and embodiment 1 is that the component regulation is different. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic in this embodiment is as follows: 0.680BiFe 0.998 Co 0.002 O3-0.320BaTiO3.
[0047] XRD spectrum of the bismuth ferrite-barium titanate-based piezoelectric ceramic material prepared in Example 5 and the piezoelectric coefficient d before and after air quenching 33 The images are Figure 1 and Figure 2 The piezoelectric coefficient d of the bismuth ferrite-barium titanate-based piezoelectric ceramics prepared in Example 5 is 33 228pC / N, increasing d 33 Compared with Examples 1 to 4, the piezoelectric coefficient d 33 And the amount of improvement has increased significantly.
[0048] Example 6 The difference between the embodiment and embodiment 1 is that the component regulation is different. The chemical formula of the bismuth ferrite-barium titanate-based piezoelectric ceramic in this embodiment is as follows: 0.670BiFe 0.998 Co 0.002 O3-0.330BaTiO3.
[0049] XRD spectrum of the bismuth ferrite-barium titanate-based piezoelectric ceramic material prepared in Example 6 and the piezoelectric coefficient d before and after air quenching 33 The images are Figure 1 and Figure 2 Example 1 Piezoelectric coefficient d of piezoelectric ceramics 33 170pC / N, increasing d 33Compared with Examples 1 to 5, the piezoelectric coefficient d 33 There is an obvious downward trend, which is due to the fact that the component with x=0.320 has the closest phase ratio, while the component with x=0.330 is more inclined to the tetragonal phase region.
[0050]
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A bismuth ferrite-barium titanate-based piezoelectric ceramic, characterized in that: The chemical formula of bismuth ferrite-barium titanate based piezoelectric ceramics is (1-x)BiFe (1-y) Co y O3-xBaTiO3, where 0.3≤x≤0.4, 0.001≤y≤0.
004.
2. The bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 1, characterized in that: The piezoelectric coefficient of bismuth ferrite-barium titanate based piezoelectric ceramics is 170~228pC / N.
3. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Using Fe2O3, Bi2O3, BaCO3, TiO2, and Co2O3 powders as raw materials, according to the stoichiometric ratio (1-x)BiFe (1-y) Co y O3-xBaTiO3 is prepared and mixed to obtain raw material powder; (2) synthesizing and finely grinding the raw material powder to obtain ceramic powder; (3) The ceramic powder is sequentially subjected to granulation, blanking, plasticizing, sintering and air quenching to obtain bismuth ferrite-barium titanate based piezoelectric ceramics.
4. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (1), the mixing process is wet ball milling, and the wet ball milling includes the following steps: Add raw materials, ball milling media and deionized water into a ball mill for ball milling until they are uniformly mixed; the mass ratio of raw materials, ball milling media and deionized water is 1: (1.6-2.4): (0.8-2); the ball milling speed is 300-400 rpm, and the ball milling time is 20-24 hours.
5. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (2), the synthesis temperature is 700-850°C, the insulation time is 4-6 hours, and the synthesis heating rate is 4-6°C / min.
6. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (2), the fine grinding process is wet ball milling, and the wet ball milling includes the following steps: The synthesized powder, ball milling medium and deionized water are added into a ball mill for ball milling until they are uniformly mixed; wherein the mass ratio of the synthesized powder, ball milling medium and deionized water is 1:(1.6~2.4):(0.8~2); the ball milling speed is 300~400 rpm, and the ball milling time is 20~24 hours.
7. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (3), during the granulation process, a binder in an amount of 5% to 10% by weight of the ceramic powder is added to carry out granulation; the binder is a 4 to 8 wt.% polyvinyl alcohol solution; The green body is made by pressing the powder into a green body with simple mechanical pressure, the molding pressure is 15~20Mpa, and the green body size is 12~14mm in diameter and 1~2mm in thickness; The temperature of plastic discharge is 600~800℃, and the heat preservation time is less than 3 hours; the heating rate of plastic discharge is ≥2℃ / minute.
8. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (3), the temperature of the debinding is 600-800°C, and the temperature is kept for less than 3 hours; the heating rate of the debinding is 4-6°C / min.
9. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (3), the sintering temperature is 980-1030° C., and the sintering time is 2-5 hours.
10. The method for preparing a bismuth ferrite-barium titanate-based piezoelectric ceramic according to claim 3, characterized in that: In step (3), the air quenching temperature is 800-970°C, the time is 20-60 minutes, and the steel sheet is taken out of the furnace directly after quenching.
Citation Information
Patent Citations
Preparation method of bismuth ferrite-barium titanate composite piezoelectric ceramic
CN111362690A
Bismuth ferrite-barium titanate lead-free piezoelectric ceramic as well as preparation method and application thereof
CN113461419A
Method for regulating and controlling resistivity and polarization intensity of bismuth ferrite-barium titanate based piezoelectric ceramic material
CN114262222A